IMPLEMENTATION OF THE NURSING THEORIES “NEED FOR HELP WIEDENBACH” AND “CONSERVATION LEVINE” IN NURSING CARE FOR PREGNANT WOMEN WITH PREECLAMPSIA - Indah Lestari; Noer Saudah (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Preeclampsia is a leading cause of maternal death during pregnancy, childbirth, and postpartum. The consequences of preeclampsia include HELLP syndrome, cardiovascular disorders, lung, kidney, and liver failure, coagulopathy, placental abruption, and cerebral hemorrhage. The consequences for the fetus include Intra-Uterine Growth Retardation (IUGR) and Intra-Uterine Fetal Death (IUFD). A comprehensive approach is needed in providing nursing care to mothers with preeclampsia. The aim of this study was to apply Wiedenbach's "Need for Help" and Levine's "Conservation" theories to the practice of nursing care for pregnant women with preeclampsia. The research method used was a case study with a focus on the application of Wiedenbach's "Need for Help" and Levine's "Conservation" theories to the practice of nursing care for pregnant women with preeclampsia. This theory was applied to two patients. Wiedenbach's theory emphasizes the importance of nurses' sensitivity in recognizing the comprehensive needs of pregnant women, including physical, psychological, and educational. Levine's theory reinforces this intervention with the principle of preserving patient integrity, which includes energy, structural, personal, and social aspects. The integration of these two theories strengthens the role of nurses as therapeutic agents who are able to manage risks, educate, and empower patients, especially pregnant women with preeclampsia.